Using Spectral-Domain Optical Coherence Tomography to Follow Outer Retinal Structure Changes in a Patient with Recurrent Punctate Inner Choroidopathy - Kimberly E. Stepien; Joseph Carroll (Journal of Ophthalmology)
Punctate inner choroidopathy (PIC) is a rare idiopathic inflammatory disorder of the retina and choroid usually affecting healthy, young, myopic females and presenting with photopsia, paracentral scotomata, and blurred vision. It is characterized by yellow-white chorioretinal lesions concentrated in the posterior pole, no vitritis, relapsing inflammatory activity of the retina and choroid, and frequent development of choroidal neovascular membranes. Here we describe a case in which spectral-domain optical coherence tomography (SD-OCT) imaging was used to monitor outer retinal structure changes associated with recurrent PIC over time. SD-OCT, which is both quantative and objective, provides an efficient, non-invasive way to follow recurrent inflammatory chorioretinal lesion activity, choroidal neovascular membrane development, and treatment response in patients with recurrent PIC.